2012
DOI: 10.2478/v10032-012-0009-y
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification of Spinach Plants APPLYING Selenium in the Nutrient Solution of Floating System

Abstract: Selenium (Se) is a very important element for human health. It is involved in defense mechanisms and biosynthesis of hormones in adult and babies. The Se is a trace element and in the human body is involved in the membrane protection and has anti-cancer action. The Se is a cofactor of glutathione peroxidase and may play an important role against oxidative tissue damage. The aim of this work was to evaluate the floating system for enriching the baby leaf plants by applying the Se directly in the nutrient soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 13 publications
3
28
0
1
Order By: Relevance
“…Se is also involved in membrane protection and has an anti-cancer action. In addition, Se plays an important role in the antioxidant protection of cells, and as a component of different enzymes such as glutathione peroxidase and thioredoxin reductase (Combs andGrey, 1998, Birringer et al, 2002;Ferrarese et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Se is also involved in membrane protection and has an anti-cancer action. In addition, Se plays an important role in the antioxidant protection of cells, and as a component of different enzymes such as glutathione peroxidase and thioredoxin reductase (Combs andGrey, 1998, Birringer et al, 2002;Ferrarese et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The recommended dietary allowance in the USA is 55 lg Se day -1 , and the reference nutrient intake in the UK is 60-75 lg Se day -1 (White and Broadley 2005). Sources: data compiled from Petry (2011) In general, food fortification with Se is a delicate task due to a very narrow safety margin between toxicity and deficiency (Ferrarese et al 2012). Therefore, biofortification using Se fertilizers must be performed under very strict conditions, since an over-accumulation in the edible parts might be toxic for consumers (Ferrarese et al 2012).…”
Section: Selenium and Its Biofortificationmentioning
confidence: 99%
“…High Se concentration in soils may not induce phytotoxic symptoms but reduces the yield of crops. The addition of Se directly in the nutrient solution allows producing enriched leafy vegetables avoiding excessive concentration in the edible parts (Malorgio et al 2009;Ferrarese et al 2012). It is reported that Se statutory maximum annual loading rates (0.15 kg ha -1 year -1 ) over a 10-year period for agricultural soils in the UK (DoE 1996) and statutory maximum cumulative metal loading rates (100 kg ha -1 ) for agricultural soils in the USA (USEPA 2000) and critical soil concentrations (11 kg ha -1 ) considered to be phytotoxic (calculating on basis a soil bulk density of 1.2 g cm -3 and a depth of 10 cm; Kabata-Pendias 2011), as reviewed by White et al (2012).…”
Section: Selenium and Its Biofortificationmentioning
confidence: 99%
See 2 more Smart Citations